Black Women’s Oppression and Resistance in Namina Forna “The Gilded Ones”: Feminist Approach - Winema Tania; Rahma Ananditha Firdaus (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
Oppression has always been experienced by black women from time to time. They have been mistreated many times by the reason of how they have always been considered as humans who have no power. And sexism, which is a discrimination based on sex or gender, have been one of the forms of the oppression. However, many of black women have shown resistance to the oppression. Therefore, the aim of this research was to find the oppression towards black women and the resistance towards the oppression in “The Gilded Ones” Novel by Namina Forna. The novel reflects black women who are under patriarchal system and have a will to fight as a form of resistance to get justice. Descriptive qualitative was used in this research, and in collecting the data, the researcher closely read the book to gain a greater knowledge of it, particularly as it relates to black feminism. The researcher then began to analyse the gender issue of black feminism's theories of oppression and resistance by Collins (2010). As the result of this research, it was shown that in “The Gilded Ones” novel, there was patriarchy happening, where male dominated female. Black women characters in the novel suffered from gendered and sexual violence. By this reason, black women characters in the novel tried to found a way and fight the oppression.